Financial Liberalization, the Weekend Effect, and Common Stock Returns in the Thai Stock Market - Chotigeat, T.; Lee, S. M. (Universiti Putra Malaysia Press, 1993)
The purpose of this study is to undertake an empirical analysis of the pattern of the daily equity returns and the day-of-the-week effect on 29 individual stocks in the financial sector of the Thai stock market over the period following the government's attempts to establish Bangkok as an international financial centre the trading time model is used to test the weekend effect, and the study confirms the test results with the nonparametric technique. The results indicate that for a portfolio of 29 stocks, as well as for most individual stocks, Monday and Tuesday returns are positive and returns for the other three days are negative. The Monday average return is the highest, while Friday has the highest volatility of return; (coefficient of variation) is higher than for Monday's returns. The test finds no evidence of the weekend effect, conforming to the pattern found in the South Korean stock market once financial liberalization got underway, and is contrary to the results from oUler small and developing Asian stock markets, such as those in Hong Kong, Singapore, Malaysia, and the Philippines. In essence, me results of this study show no evidence to support the inherent inefficiency of the Thai stock market as has been proposed in previous studies.